miRNA-223 suppresses FOXO1 and functions as a potential tumor marker in breast cancer - Wei, Y-T.; Guo, D-W.; Hou, X-Z.; Jiang, D-Q. (Cellular and Molecular Biology, 2017)
Breast cancer is the most commonly diagnosed cancer in women and a leading cause of cancer mortality. MicroRNAs (miRNAs) have been found to play a key role in proliferation, metastasis and invasion of cancer. In previous study, we found that miRNA-223 was significant expression inexosome derived from peripheral blood serum of breast cancer patients than in samples from control subjects, Therefor,the role ofmiRNA-223willbe researched in MCF-7 breast cancer cells.In this study, to explore the role of miRNA-223in influencing cell proliferation, metastasis and invasion of breast cancer, TargetScan tools (http://www.targetscan.org/vert_71/) was used to scan target genes of miRNA-223, and thenmiRNA expression, real time PCR, Western blotting andluciferase report assay were used to test regulates relationship of miRNA-223and its targets,cell viability and BrdU analysiswere used to test cell proliferation of MCF-7 breast cancer cells after expression miRNA-223inhibitor. Scanning targets of miRNA-223found FOXO1 was listed in targets content, and luciferase reporter assay was used to assess and confirm the binding sequence of 3"²untranslated region between FOXO1 and miRNA-223. Results showedthat miRNA-223inhibitorexpression increased protein expression level of FOXO1 in MCF-7 breast cancer cells,meanwhile, cell viability and BrdU analysis showed MCF-7 breast cancer cells were suppressed proliferation after up-regulation of FOXO1.In conclusion, we demonstrated that the miRNA-223can maintain cell proliferation of breast cancer cell through targeting FOXO 1, these results provide a new insight in tumor marker and potential therapeutic targets for breast cancer.